PENGARUH TINGKAT PENGHASILAN KELUARGA TERHADAP KETERLAMBATAN PENCARIAN PENGOBATAN PASIEN TUBERKULOSIS PARU DI KABUPATEN BANYUMAS - Maryoto, Madyo; Khasanah, Suci (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2017)
The tuberculosis cases due to be a source of infection for people in the neighborhood, so it needs an increase in efforts to find active case (MOH, 2001) , Delays in treatment lead to the transmission, as well as the impact the increased risk of disease transmission. So search delays pulmonary TB treatment resulted in increased numbers of cases of pulmonary TB. Objectives of this study was to analyze the delay of treatment seeking behavior  of Pulmonaru TB patients in Banyumas Regency. The study design using analytic descriptive study. Samples in this study were patients who had intensive phase of TB treatment (first 2 months) in Primary Health care center of Banyumas regency. The sample size of this study were 102 respondents, purposive sampling technique was used in this study. In which the variables includes:   family income and delay seeking treatment of TB patients. Analysis of this study was use simple logistic regression. The result of this study shows that the majority of pulmonary TB patients were not delay in seeking of treatment. It was about 56 respondents (54.9%). There is influence  between family income  and the delay treatment seeking behavior of pulmonary TB patients in Banyumas Regency.  . Keywords:   Family Income,  The Delay Treatment Seeking Behavior, TB